Network Governance dalam Pengembangan Destinasi Wisata Berbasis Masyarakat di Kota Lama Tanjungpinang - Nurul Hasanah; Fitri Kurnianingsih; Chaereyranba Sholeh (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Tanjungpinang City in the Riau Islands has tourism potential, but the number of tourists has decreased due to the COVID-19 outbreak and has not fully recovered. The revitalization of Kota Lama Tanjungpinang is one of the efforts to increase tourist attractiveness by involving the active role of the community through network governance. This research aims to understand Network Governance in the development of community-based tourist destinations in Kota Lama Tanjungpinang, as well as its obstacles and success factors. Using a qualitative approach with observation, interviews, and documentation. In conclusion, this study found that coordination between the government, NGOs (Non-Governmental Organization), and the community was effective but not optimal. This research suggests increasing cooperation and coordination between the government and related parties in the development of community-based tourist destinations in Kota Lama Tanjungpinang.